1995
DOI: 10.1016/0735-1097(95)00124-i
|View full text |Cite
|
Sign up to set email alerts
|

Coronary angioplasty, atherectomy and bypass surgery in cardiac transplant recipients

Abstract: Coronary revascularization may be an effective palliative therapy in suitable cardiac transplant recipients. Angioplasty has an acceptable survival in patients without angiographic distal arteriopathy. Because few patients underwent atherectomy and coronary bypass surgery, assessment of these procedures is limited. Angiographic distal arteriopathy is associated with decreased allograft survival in patients requiring revascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
109
0
3

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 182 publications
(113 citation statements)
references
References 44 publications
1
109
0
3
Order By: Relevance
“…1,2 Although various interventional revascularization methods have been used to treat TCAD, it is still unknown whether angioplasty-based therapies prolong cardiac allograft or patient survival. 12,14 The procedural success rate was 93% (145 of 156 lesions) in the present study. Previous studies of PCI for TCAD reported a similar initial success rate.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…1,2 Although various interventional revascularization methods have been used to treat TCAD, it is still unknown whether angioplasty-based therapies prolong cardiac allograft or patient survival. 12,14 The procedural success rate was 93% (145 of 156 lesions) in the present study. Previous studies of PCI for TCAD reported a similar initial success rate.…”
Section: Discussionmentioning
confidence: 62%
“…Allograft survival (defined as the absence of retransplantation or death) was maintained in 32 of 65 patients (49%) a mean of 35 Ϯ 30 months after the successful initial PCI. In a multicenter review, Halle et al 14 reported in 1995 that 61% (40 of 66 patients) were alive without repeat OHT at 19 Ϯ 14 months after angioplasty, but the Kaplan-Meier actuarial survival was only 20% at 5 years after angioplasty. Several explanations may exist as to why the actuarial survival was improved in the present study; these include alterations in surgical technique, newer medical regimens, and the use of coronary stents and DESs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though not completely clarified, we believe that allograft vasculopathy results from an immunologically mediated phenomenon aggravated by atherogenic involvement. When the histologic characteristics of the coronary artery lesion are analyzed, we observe a predominance of macrophages and cytotoxic T lymphocytes, proliferation of smooth muscle cells, and myointimal hyperplasia, resulting in concentric luminal stenosis, which is also found in early restenosis following angioplasty 11,12 . Some immune and nonimmune risk factors seem to contribute to the development of the disease; this issue, however, remains controversial.…”
mentioning
confidence: 99%
“…This restenosis rate is high compared with conventional balloon angioplasty for cardiac allograft arteriopathy. 4,5,8 We initially suspected the high restenosis rate associated with use of the Cutting Balloon was a manifestation of the aggressive proliferation seen with this patient population rather than a direct effect of Cutting Balloon angioplasty when used in transplanted arteries. However, the Cutting Balloon itself might exacerbate the aggressive tissue proliferation associated with transplant arteriopathy and result in a high restenosis rate.…”
Section: Cutting Balloon Angioplasty For Allograft Arteriopathymentioning
confidence: 99%